ESCO2 inhibition induces cell cycle arrest and apoptosis in breast cancer via the P53-CDK1 axis and the BAX/Bcl2/caspase signaling cascade - Li, Pingchuan; Wei, Lineng; Li, Meng; Liu, Xiaoqiang; Yang, Huawei (Frontiers in Oncology, 2025)
BackgroundBreast cancer is a major threat to women’s health, and dysregulation of the cell cycle is a critical driver of its progression. ESCO2, a potential key regulator of the cell cycle, is implicated in cancer development; however, its specific role and mechanisms in breast cancer remain poorly understood.MethodsWe analyzed differentially expressed genes between breast cancer and normal breast samples from GEO datasets to identify potential key regulators of the cell cycle pathway. ESCO2 expression was further investigated in breast cancer cell lines. Functional assays, including overexpression and knockdown of ESCO2 in MDA-MB-231 and MDA-MB-468 cells, were performed to assess its effects on the cell cycle and apoptosis. Molecular mechanisms were explored using Western blot, and rescue experiments were conducted to validate key regulatory pathways.ResultsAnalysis of the GSE38959 and GSE70947 datasets identified 541 common differentially expressed genes, with 26 genes enriched in the cell cycle pathway. ESCO2 interacted with multiple cell cycle-related genes and was significantly overexpressed in breast cancer. Overexpression of ESCO2 promoted DNA replication, while its knockdown induced G2/M phase arrest via the ESCO2-P53-CDK1 regulatory axis, and triggered apoptosis through the BAX/Bcl2/caspase9/caspase7 signaling cascade. The effects of ESCO2 knockdown on the cell cycle and apoptosis were rescued by siP53.ConclusionOur findings reveal that ESCO2 is upregulated in breast cancer and may contribute to cell cycle regulation and apoptosis through the p53-CDK1 and BAX/Bcl-2-caspase pathways. These results highlight ESCO2 as a potential therapeutic target and provide new mechanistic insights into breast cancer progression.